Handwriting in early America : a media history - Mattes, Mark Alan, 1982-; Sánchez-Eppler, Karen (Studies in print culture and the history of the book., 2023)
"As digital communication has become dominant, commentators have declared that handwriting is a thing of the past, a relic of an earlier age. This volume of original essays makes it clear that anxiety around handwriting has existed for centuries and explores writing practices from a variety of interdisciplinary fields, including manuscript studies, Native American studies, media history, African American studies, book history, bibliography, textual studies, and archive theory. By examining how a culturally diverse set of people grappled with handwriting in their own time and weathered shifting relationships to it, Handwriting in Early America uncovers perspectives that are multiethnic and multiracial, transatlantic and hemispheric, colonial and Indigenous, multilingual and illiterate. Essays describe a future of handwriting as envisioned by practitioners, teachers, and even government officials of this time, revealing the tension between the anxiety of loss and the need to allow for variations going forward"